Association of intracranial aneurysm rupture with smoking duration, intensity, and cessation. (26th September 2017) - Can, Anil; Castro, Victor M.; Ozdemir, Yildirim H.; Dagen, Sarajune; Yu, Sheng; Dligach, Dmitriy; Finan, Sean; Gainer, Vivian; Shadick, Nancy A.; Murphy, Shawn; Cai, Tianxi; Savova, Guergana; et al.
Abstract : Objective: Although smoking is a known risk factor for intracranial aneurysm (IA) rupture, the exact relationship between IA rupture and smoking intensity and duration, as well as duration of smoking cessation, remains unknown. Methods: In this case-control study, we analyzed 4, 701 patients with 6, 411 IAs diagnosed at the Brigham and Women's Hospital and Massachusetts General Hospital between 1990 and 2016. We divided individuals into patients with ruptured aneurysms and controls with unruptured aneurysms. We performed univariable and multivariable logistic regression analyses to determine the association between smoking status and ruptured IAs at presentation. In a subgroup analysis among former and current smokers, we assessed the association between ruptured aneurysms and number of packs per day, duration of smoking, and duration since smoking cessation. Results: In multivariable analysis, current (odds ratio [OR] 2.21, 95% confidence interval [CI] 1.89–2.59) and former smoking status (OR 1.56, 95% CI 1.31–1.86) were associated with rupture status at presentation compared with never smokers. In a subgroup analysis among current and former smokers, years smoked (OR 1.02, 95% CI 1.01–1.03) and packs per day (OR 1.46, 95% CI 1.25–1.70) were significantly associated with ruptured aneurysms at presentation, whereas duration since cessation among former smokers was not significant (OR 1.00, 95% CI 0.99–1.02). Conclusions: Current cigarette smoking, smoking intensity, and smoking duration are significantly associated with ruptured IAs at presentation. However, the significantly increased risk persists after smoking cessation, and smoking cessation does not confer a reduced risk of aneurysmal subarachnoid hemorrhage beyond that of reducing the cumulative dose.